ULTRASONIC PULSE MEASUREMENTS IN ANISOTROPIC LAKE ICE. - Roethlisberger,Hans (1966)
Travel-time measurements of ultrasonic pulses were carried out in March 1960 on Lake Superior (Keweenaw Bay) near Barage, Mich. The ice was about 45cm thick and consisted of grains with vertical c-axis orientation with the exception of a surface layer of variable thickness. Ultrasonic pulses were transmitted and received by barium titanate cells of cylindrical and spherical shape. The transducers were mounted at the surface and the distance was varied. Several direct and reflected signals could be identified. Of the reflected events, the PS type were the clearest and strongest at distances many times the ice thickness, and thus best suited for ice thickness determination. In order to obtain satisfactory agreement between theoretical and measured travel times the anisotropy of the ice had to be taken into account. The elastic constants determined by Bass et al. (1957) gave reasonable good agreement between computed and measured travel time, but some discrepancies remain to be explained. Part of the observed reflections occurred on cracks in the ice. Using equipment with approximately 100-kc signals the ice thickness was determined by the ultrasonic pulse method, destruction free, with an accuracy of 2-4 cm or 5-10%. For day-to-day comparisons the relative accuracy would be in the order of 0.5 cm. (Author)